Selective synthesis of secondary amines from nitriles by a user-friendly cobalt catalyst - Sharma, Dipesh M.; Punji, Benudhar (Advanced Synthesis & Catalysis, 2019)
Selective hydrogenation/reductive amination of nitriles to secondary amines catalyzed by an inexpensive and user-friendly cobalt complex, (Xantphos)CoCl2, is reported. The use of (Xantphos)CoCl2 and ammonia borane (NH3-BH3) combination affords the selective reduction of nitriles to symmetrical secondary amines, whereas the employment of (Xantphos)CoCl2 and dimethylamine borane (Me2NH-BH3) along with external amines produce unsymmetrical secondary amines and tertiary amines. The general applicability of this methodology is demonstrated by the synthesis of 43 symmetrical and unsymmetrical secondary and tertiary amines bearing diverse functionalities.